Association Between Psoriasis and Subclinical Atherosclerosis: A Meta-Analysis. Issue 20 (May 2016) - Fang, Na; Jiang, Menglin; Fan, Yu
Abstract : Abstract: The association between psoriasis and carotid intima-media thickness (CIMT) or impaired flow-mediated dilation (FMD) remains controversial. We aimed to evaluate the extent of subclinical atherosclerosis as measured by CIMT and FMD in patients with psoriasis by conducting a meta-analysis. A systematic literature search was performed using PubMed, Embase, Cochrane databases, China National Knowledge Infrastructure, and VIP databases up to February 2015. Observational studies investigating CIMT or FMD in patients with psoriasis and controls were eligible. Psoriatic patients and controls were at least age- and sex-matched. Random-effects analysis was used to estimate the weighted mean difference (WMD) and 95% confidence interval (CI) between psoriatic patients and controls. A total of 20 studies were identified and analyzed. Meta-analysis showed that psoriatic patients had a significantly thicker CIMT (WMD 0.11 mm; 95% CI 0.08–0.15) and lower FMD (WMD −2.79%; −4.14% to −1.43%) than those in controls. Subgroup analysis indicated that psoriatic arthritis appeared to have less impaired FMD (WMD −2.45%) and thinner CIMT (WMD 0.10 mm). Psoriatic patients with mean age >45 years had much thicker CIMT (WMD 0.13 mm). The impaired FMD (WMD −3.99%) seemed more pronounced in psoriatic patients with mean age <45 years. This meta-analysis suggests that patients with psoriasis are associated with excessive risk of subclinical atherosclerosis. Screening and monitoring CIMT and brachial artery FMD may be recommended to identify a subgroup of psoriatic patients at higher risk for cardiovascular events.